Manipulação térmica embrionária e diferentes níveis de treonina na resposta de frangos Label Rouge desafiados com Salmonella enteritidis - Azevedo, Alessandra Reigado Eliezer Gomes de (2016)
The effects of thermal manipulation during incubation and dietary threonine levels on Label Rouge birds challenged with Salmonella Enteritidis were assessed in the present study. Two hundred and forty fertile eggs of Naked Neck birds were weighed and distributed in three artificial incubators set to 37.7 ºC and 60% of relative humidity. At the eleventh day of incubation (DE11), the temperature of the incubators were set to one of the following treatments: cold (36.7ºC), standard (37.7ºC) and high incubation temperature (38.7ºC). After hatching the birds were distributed according to a 3x2+1 factorial (three incubation temperatures, two threonine levels and sham control). Two-day old chicks were inoculated with S. Enteritidis (1.9 x 107 UFC/mL), except for the sham control birds. Eight days after inoculation, all birds were weighed and slaughtered for sampling. High incubation temperature and high threonine levels improved the response of birds to Salmonella Enteritidis, a shown by improved performance and intestinal integrity, lower colonization and number of infected birds.